People in arms and radical thinking: Marxism and Guevarism in Helio Gallardo's Theoretical-Political Definitions - Herrera Zúñiga, José Roberto (2025)
This article is a first characterization of Helio Gallardo’s political thought, which is intended to be a broader investigation on how Gallardo has characterized the processes of democratization in Latin America and the ways of being politically people («serpolíticamente pueblo») during the period 1989-2006. The paper investigates the production of theoretical concepts in Helio Gallardo by examining his elaborations between 1977 and 1990. Finally, from a theoretical perspective anchored in classical Marxism, we make a series of critiques of Gallardo’s understanding of radical thinking.